Determining the Stage of Kaposi Sarcoma Through Histopathological Analysis: Identifying The Most Effective Finding: Effective Histopathological Findings for Staging Kaposi Sarcoma - Anique, Muhammad; Akhlaq, Humera; Azhar, Sarah; Jahan, Amna; Kazi, Jehangir; Soomro, Qandeel Abbas (Pakistan Journal of Health Sciences, 2024)
Kaposi Sarcoma (KS) is a complex disease presenting as vascular tumors affecting the skin, mucous membranes, lymph nodes, and internal organs. It shows variable clinical presentations and forms. Objective: To identify the most effective histopathological indicators for staging Kaposi Sarcoma. Methods: This cross-sectional study was conducted at Bithai Medical and Dental Center, Mirpur Khas, from December 2022 to December 2023. A total of 119 biopsy specimens were analyzed for spindle cell density, arrangement, atypia, vascular space formation (size and morphology), inflammatory cells (lymphocytes, plasma cells), hemosiderin extent and distribution, and mitotic activity. Data analysis was performed using SPSS version 24.0. Results: The study included 38 males (31.93%) and 81 females (68.07%). The nodular stage was most prevalent (72 cases, 60.5%), followed by the patchy stage (29 cases, 24.37%) and plaque stage (18 cases, 15.12%). Significant histopathological findings included spindle cell proliferation in 62 cases (52.11%), vascular space formation in 39 cases (32.77%), inflammatory infiltrate in 31 cases (26.05%), hemosiderin deposits in 43 cases (36.13%), and mitotic activity in 35 cases (29.41%). Conclusions: Spindle cell proliferation and vascular space formation are the most reliable indicators for staging KS. Inflammatory infiltrate composition, hemosiderin deposits, and mitotic activity showed less consistency across different specimens